2008
DOI: 10.1103/physrevlett.100.143902
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Path Interferences in High-Order Harmonic Generation

Abstract: We have investigated the intensity dependence of high-order harmonic generation in argon when the two shortest quantum paths contribute to the harmonic emission. For the first time to our knowledge, experimental conditions were found to clearly observe interference between these two quantum paths that are in excellent agreement with theoretical predictions. This result is a first step towards the direct experimental characterization of the full single-atom dipole moment and demonstrates an unprecedented accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
141
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 198 publications
(159 citation statements)
references
References 28 publications
13
141
2
1
Order By: Relevance
“…2. Consequently, propagation, phase matching or QPI, in contrary to previous works [22][23][24][25][26]31 , are not the dominant mechanisms driving the spatio-spectral structures that we observed. The key parameters are the nonlinearity of the atomic response, its saturation and the depletion of the ground state so that the harmonic source is shaped spatially and temporally during the generation process.…”
Section: Article Nature Communications | Doi: 101038/ncomms5637contrasting
confidence: 55%
See 3 more Smart Citations
“…2. Consequently, propagation, phase matching or QPI, in contrary to previous works [22][23][24][25][26]31 , are not the dominant mechanisms driving the spatio-spectral structures that we observed. The key parameters are the nonlinearity of the atomic response, its saturation and the depletion of the ground state so that the harmonic source is shaped spatially and temporally during the generation process.…”
Section: Article Nature Communications | Doi: 101038/ncomms5637contrasting
confidence: 55%
“…They indicated that the structures are due to the spatial coherence of the emission and its rapid temporal evolution. They can also be obtained with a single quantum path (see Supplementary Figs 4,5), which confirm that they are created by a different process than QPI [22][23][24][25] . Note that the fine details of the structures highly depend on several parameters, such as the intensity spatial profile and amplitude (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 49%
See 2 more Smart Citations
“…The proportional constant α i=S, L depends on "short" (S) or "long" (L) trajectories. The phase can also be expressed in terms of the ponderomotive energy U p and the electron excursion time τ q i : ϕ q i ≈ −β i U p τ q i [154], where the coefficient β i for the "short" trajectory is much smaller than for the "long" trajectory. The electron excursion times for the two trajectories are τ q S ≈ T /2 and τ q L ≈ T (T is the laser period) [38].…”
Section: Time-frequency Analysis Of Harmonics In Near and Far Fieldsmentioning
confidence: 99%